2019
DOI: 10.1155/2019/4610458
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive Symptoms and Associated Factors among HIV-Positive Youth Attending ART Follow-Up in Addis Ababa, Ethiopia

Abstract: Depression is most frequently and highly occurring common mental disorder in HIV/AIDS patients especially youth living with HIV/AIDS. This study aimed to assess the prevalence and associated factors of depressive symptoms among youth living with Human Immunodeficiency Virus (HIV) attending Antiretroviral Therapy (ART) follow-up at public hospitals in Addis Ababa, Ethiopia. Objective. To assess the prevalence and associated factors of depressive symptoms among youth living with Human Immunodeficiency Virus (HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 24 publications
16
67
1
Order By: Relevance
“…This indicated that acquiring another illness was considered by these women to be risky, in a situation where dealing more symptoms from chronic illnesses consistently over some time. Consistent with these ndings, similar studies have narrated that acquiring comorbid illnesses have increased the rate of depression among People Living with HIV (6,(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 68%
“…This indicated that acquiring another illness was considered by these women to be risky, in a situation where dealing more symptoms from chronic illnesses consistently over some time. Consistent with these ndings, similar studies have narrated that acquiring comorbid illnesses have increased the rate of depression among People Living with HIV (6,(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 68%
“…Of the ten quantitative studies ( Table 2), five were conducted in southern Africa: South Africa [90,91], Namibia [92], Malawi [93], Zambia [94] ( Table 3). The remainder conducted in eastern Africa: Uganda (n = 2) [95,96], Kenya (n = 1) [97], Ethiopia (n = 1) [98] and Tanzania (n = 1) [99]. All studies employed a crosssectional study design.…”
Section: Quantitative Studies-characteristics and Data Synthesismentioning
confidence: 99%
“…iii. Psycho-social HIV-related stigma was strongly positively associated with poor mental health functioning in six studies [91,92,94,96,98,99]. Among these studies, the largest effect of stigma was documented in Zambia, which found that the odds of having higher depressive symptom scores was almost three times higher for YPLHIV who experienced stigma than in those who did not (aOR = 2.99; 95% CI [1.07-8.41], p = 0.01) [94].…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations